Pengaruh Fasilitas dan Design Layout terhadap Keputusan Penggunaan Jasa Event pada Muda Art Project Event Organizer - Ara Putri Sakita; Dewi Comala Sari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Facilities are everything such as objects, buildings or rooms that are made to serve / facilitate carrying out certain goals or are facilities and infrastructure for carrying out certain activities. The definition of layout in general is a determination of the layout design on certain elements so as to produce an attractive visual. The purpose of this study was to determine whether there is an influence of facilities and Design layout on the decision of event service users at Muda Art Project Event Organizer. This research is a type of associative research that uses quantitative data with a sample size of 44 people, namely Map Event Organizer clients from 2019-2023. The data analysis technique used in this research is multiple linear regression with partial data hypothesis testing (t test), simultaneous test (f test) and the coefficient of determination. The test results of this study obtained that the facility variable has a positive and significant influence on the decision of event service users and the Design layout variable has no positive and insignificant effect on the decision of event service users. Simultaneously or simultaneously facilities and Design layout have a significant influence on the decision of event service users at Muda Art Project Event Organizer.